Journalistic media and adolescents in the COVID-19 pandemic: a documental analysis - Marcela Claudia de Paula Oliveira; Emilia Chagas Costa; Lygia Maria Pereira da Silva; Livia Novaes Vieira Barbosa; Mauro Virgilio Gomes de Barros; José Henrique Cavalcanti Mota Filho; Marco Aurelio de Valois Correia Junior (Sociedade de Pediatria de São Paulo, 2023)
ABSTRACT Objective: To analyze how the journalistic media has described the issues of quality of life (QoL), physical activity (PA) and mental health (MH) of adolescents during the COVID-19 pandemic. Methods: This is a descriptive and qualitative study that used content analysis. Sixty-two journalistic publications were analyzed from a total of 8211 published by the most read newspapers in each Brazilian region between December 2019 and August 2021. Results: The results were grouped and evaluated in three categories: QoL (n=11), PA (n =9) and MH (n=42). In the analyzed period, the adolescents had more time of exposure to screens, contributing to an inadequate diet, a decrease in PA and impairments in QoL. According to the media publications, the pandemic has also contributed to an increase in anxiety, depression, loneliness and fear resulting from the mental and emotional disorganization caused by the abrupt change in routine. Social vulnerability was presented as an aggravating factor in this context. The journalistic media did not pay the necessary attention to adolescents regarding the negative consequences of the pandemic on QoL, PA and MH. Conclusions: The analyzed reports showed that the pandemic caused a decrease in social interaction, feelings of uncertainty, fear and the appearance/exacerbation of symptoms of anxiety, stress and depression. Social vulnerability was presented as another obstacle to be faced in this problem.